Benign and malignant papillary lesions of the breast: Radiographic differentiation by mammography and sonography - Thongsongsom, Thiti; Chayakulkheeree, Jatuporn (Chulalongkorn Medical Journal, 2023)
Background : There has been limited data regarding the radiographic features related to malignant papillary lesions and no features to definitely differentiate between benign and malignant papillary lesions. Objective : To determine the mammographic and sonographic features and their detection rate for differentiation of benign and malignant papillary lesions. Design : A retrospective analytic study Setting : Department of Radiology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand Methods : We retrospectively reviewed mammography and sonography of 89 surgically proven benign papillary lesions and 44 malignant papillary lesions from January 1, 2005 to December 31, 2014 at our institution. Radiographic findings were analyzed according to the Breast Imaging Reporting and Data System. Results : Of these 133 papillary lesions, 50.4% (67/133) and 97.7% (130/133) could be detected on mammography and sonography, respectively. An irregular shape, non-circumscribed margin, high density of mass and suspicious calcification were more frequently found on mammography in malignant lesions (P < 0.05). As for sonography, an irregular shape, complex or heterogeneous echo of mass, intralesional vascularity and suspicious calcification were more frequently found in malignant lesions (P < 0.05). When combining interpretation of mammography and sonography, they gave a sensitivity of 97.7%, specificity of 36%, positive predictive value of 43%, and negative predictive value (NPV) of 97%. Conclusions : Although there were some overlaps of radiographic features between benign and malignant papillary lesions, we found the features significantly indicative of malignant papillary lesions and gave high sensitivity and NPV. In the future, if histopathologic diagnosis of the papillary lesions is benign on core-needle biopsy and concordant with benign radiographic findings, conservative management with follow-up imaging instead of surgical excision may be considered.